Personal finance - Callaghan, George; Fribbance, Ian; Higginson, Martin (London Palgrave Macmillan, 2012)
Personal Finance is an innovative text that builds confidence and competence in making personal financial decisions. Using a socio-economic approach to personal finance, it illuminates the many factors and relationships that help improve financial capability.